2015
DOI: 10.1021/acscatal.5b01429
|View full text |Cite
|
Sign up to set email alerts
|

Metal Phosphides Derived from Hydrotalcite Precursors toward the Selective Hydrogenation of Phenylacetylene

Abstract: We report a new synthetic strategy for the fabrication of several supported nickel phosphides (Ni 12 P 5 , Ni 2 P, and NiP 2 ) with particle size ranging in 5−15 nm via a two-step procedure: preparation of supported Ni particles from layered double hydroxide precursors, followed by a further reaction with certain amount of red phosphorus. The selective hydrogenation of phenylacetylene over these metal phosphides was evaluated, and the as-prepared Ni 2 P/Al 2 O 3 catalyst show a much higher selectivity to styre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
110
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 65 publications
4
110
0
2
Order By: Relevance
“…However, the spectra of these samples (Figure a) do not show significant edge‐shift as reported for phosphides but rather a systematic increase of the peak P2 intensity and correspondingly a decrease of the P1 resonance. P2 is significantly pronounced in the Ni/SiO 2 _5x0.75y spectrum, resembling NiO XANES spectra reported in the literature . Based on this, we propose that the samples are composed of a mixed Ni oxide and metallic phases, whereby spectral variations amongst the samples account for changes in composition of the two phases.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…However, the spectra of these samples (Figure a) do not show significant edge‐shift as reported for phosphides but rather a systematic increase of the peak P2 intensity and correspondingly a decrease of the P1 resonance. P2 is significantly pronounced in the Ni/SiO 2 _5x0.75y spectrum, resembling NiO XANES spectra reported in the literature . Based on this, we propose that the samples are composed of a mixed Ni oxide and metallic phases, whereby spectral variations amongst the samples account for changes in composition of the two phases.…”
Section: Resultssupporting
confidence: 82%
“…Furthermore, we note that previous literature on Ni phosphides has indicated that the radial distribution function presents pronounced changes with the content of P and that the FT EXAFS of the Ni/SiO 2 _5x3y sample is similar to the spectrum reported for a Ni 12 P 5 phase with a calculated oxidation state of 0.43 . Therefore, it could also be possible that the Ni/SiO 2 _5x3y sample might contain a small amount of P as an amorphous phase, as we would have expected considering that the OAm:TOP ratio used in its synthesis was similar to the one used in the preparation of the unsupported Ni _2.5x1.5y sample.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The lattice fringes with spacing of 0.221, 0.193 and 0.180 nm corresponded to the (111) plane of Ni 2 P, (240) plane of Ni 12 P 5 and (222) plane of Ni 3 P. The XPS investigations showed that the Ni 2p 3/2 edges in the three nickel phosphides were deconvolved into three peaks (Figure ). The peaks at 853.0, 852.7 and 852.4 eV were assigned to the positive charge Ni δ+ for Ni 2 P, Ni 12 P 5 and Ni 3 P, respectively . The value of δ was δ(Ni 2 P)>δ(Ni 12 P 5 )>δ(Ni 3 P).…”
Section: Resultsmentioning
confidence: 99%
“…2000 times cheaper than palladium) [20,21] and of the abundance and hydrogen splitting ability of this metal, nickel phosphides have also attracted interest for alkyne semihydrogenation, although only a few contributions have evaluated their activity. In this respect, Corma and coworkers [22] assessed colloidal nickel phosphides in the semi-hydrogenation of functionalized alkynes, while bulk Ni x P y phases were prepared by thermal treatment of hydrotalcite-like compounds containing Ni and tested in phenylacetylene hydrogenation by Chen et al [23] These two contributions showed that the well-known unselective behavior of bare nickel [9,10] can be modulated by treatment with phosphorus. Similar findings have been recently extrapolated by Anderson et al [24] to nanostructured palladium phosphide catalysts for gas-phase applications.…”
Section: Introductionmentioning
confidence: 99%